Measurement of human dentin Sialoprotein in healthy and decay teeth - D.Qujeq (Ph.D) (مجله دانشگاه علوم پزشکی گرگان, 2001)
Sialoprotein is one of the most abundant non-collageneous and phosphorylated glycoproteins in human. This protein plays an important role in the structure of human teeth. The aim of this project is to measure the amount of dentin Sialoprotein in the healthy and decay teeth to evaluate the variation in the teeth structure. In this investigation 50 decay teeth has been collected from patients referred to the clinic. The dentin was separated and placed in liquid Nitrogen. One gram of each dentin was washed with distilled water for 30 mins and subsequently the dentin was powdered, and relocated to the gaunidin-Hcl tris buffer, and incubated at 4°C for 48 hrs. The dentin powder was centrifuged at 3000 g for 20 mine. The supernatant was discarded, and the samples again was centrifuged at 10000 g. Finally one ml of this supernatant transferred to the sepharose column and washed with gaunidin-Hcl tris at 1 ml/min. The fractions obtained by chromatography was monitored by electrophoresis. The amount of decay teeth Sialoprotein was 17.23±1.45 ng/l and in the healthy teeth was 26.39±4.27 ng/l. The results from this study indicate that the Sialoprotein content in patient dentin decreased by about 1.5 time compared normal subjects.